LITERASI BUDAYA KEWARGAAN DALAM PENDIDIKAN POLITIK BAGI WARGA NEGARA MUDA - Lambertus Kollo , Fredik; G. Henukh, Giovani; Otemusu, Chory J (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
Civic cultural literacy as an effort to strengthen political education for citizens to get to know culture so that family-based politics can be built. This study aims to know and analyze civic cultural literacy as an effort in political education. The method used in this research is qualitative literature study by collecting data from various literature. The results of this study show that civic cultural literacy provides understanding for citizens to know culture well and political education provides understanding for citizens to know the political system in Indonesia. Socialization as a form of political education in providing or transferring political knowledge to young citizens. Political education provides understanding for citizens to be able to do politics well as the cultural heritage of the predecessors. Gotong royong as a culture of Indonesian society that must be preserved in various demensions of people's lives including political dimensions.